Investigation of survivability for insects subjected to injection and implantation of foreign materials and to electrical stimulation of neuromuscular sites - Chui, Yi Hun (2019)
This paper aims to test the survivability and usability of the beetles, Dicronorrhina derbyana, when subjected to stimulation of muscles, optic lobes, exposure of muscles and when they are injected with various solutions. Each scenario will be experimented on each beetle individually. No combinations of test will be conducted on beetles. The results were analysed to provide a further understanding of the limits of the beetle. Through these findings, a greater understanding of the capacity of the beetles can be better predicted.